Disney's Winnie the Pooh's Halloween - Talkington, Bruce; Vaccaro Associates (New York : Disney Press, 1993)
On Halloween night Winnie the Pooh and all his friends get ready to put on their scariest costumes, but Piglet plans to spend Halloween tucked safely away under his bed.
7 9 13 26
Keywords: Halloween -- Fiction; Winnie-the-Pooh (Fictitious character) -- Fiction; Toys -- Fiction